2010
DOI: 10.1186/1471-2458-10-633
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of primary hepatitis C infection and risk factors for transmission in an Australian prisoner cohort

Abstract: BackgroundHepatitis C virus (HCV) infection is common in prisoner populations, particularly those with a history of injecting drug use (IDU). Previous studies of HCV incidence have been based on small case numbers and have not distinguished risk events in prison from those in the community.MethodsHCV incidence was examined in a longitudinal cohort of 488 Australian prisoners with a history of IDU and documented to be seronegative within 12 months prior to enrolment. Inmates were tested for anti-HCV antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 32 publications
5
79
1
1
Order By: Relevance
“…Samples from a prospective cohort of 500 HCV seronegative high-risk inmates enrolled in the Hepatitis C Incidence and Transmission Study in prisons (HITS-p) collected between 2005 and 2013 were used in this study (31)(32)(33). Inmates were enrolled in 34 correctional centers across New South Wales, Australia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples from a prospective cohort of 500 HCV seronegative high-risk inmates enrolled in the Hepatitis C Incidence and Transmission Study in prisons (HITS-p) collected between 2005 and 2013 were used in this study (31)(32)(33). Inmates were enrolled in 34 correctional centers across New South Wales, Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected every 6 months to screen for seroconversion and for HCV RNA positivity, and upon diagnosis of incident infection, three to six samples were collected monthly. Details of the study protocol were reported elsewhere (16,(31)(32)(33) Virological assessments. All sera were tested for HCV antibodies using the Abbott Architect anti-HCV chemiluminescent microparticle immunoassay (Abbott Diagnostics, Abbott Park, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, following detection of initial viremia, blood samples were collected frequently over a 24-week period until spontaneous clearance or chronic infection was established. HCV antibody (Ab) and HCV RNA testing was performed as described previously (25). The date of infection for each subject was estimated by subtracting the recognized mean preseroconversion window period of 51 days from the midpoint between the last HCV RNA-positive/HCV Abnegative time point and the first seropositive time point (26).…”
Section: Methodsmentioning
confidence: 99%
“…Our findings also are below the HCV incidence observed previously in a Scottish prison [16] and among the lowest reported incidence internationally. These range from 0.4 to 15.0 per 100 person-years overall and from 5.5 to 34.2 per 100 person-years among prisoners with an injecting history [17,25,[40][41][42][43]. It is recognized that injecting risk in prison is high, as most events involve sharing unsterile equipment [39,44].…”
Section: Study Findings In Relation To Other Evidencementioning
confidence: 99%
“…Our survey suggests that, even though there is likely to be under-reporting, a minority of people inject in prisons in Scotland and that injecting frequency is low compared to other studies. For example, two studies reported high HCV incidence levels and injecting occurrence of 34.2 and 31.6 per 100 person-years and 34 and 27%, respectively, among people with an injecting history [17,43]. Comparable studies, however, are difficult to find because of heterogeneity in recruitment, sampling, prisoner characteristics and definitions of prison transmission [22,25,42].…”
Section: Study Findings In Relation To Other Evidencementioning
confidence: 99%